Impact of a short-term nitrate and citrulline co-supplementation on sport performance in elite rowers: a randomized, double-blind, placebo-controlled crossover trial - Viribay, A.; Alcantara, J. M. A.; López, I.; Mielgo-Ayuso, J.; Castañeda-Babarro, A. (European Journal of Applied Physiology, 2024)
Purpose Citrulline (CIT) and beetroot extract (BR) have separately shown benefits in rowing performance-related outcomes. However, effects of combined supplementation remain to be elucidated. The main purpose of this research was to study the effects of 1 week of daily co-supplementation of 3.5 g BR (500 mg NO3-) plus 6 g CIT on aerobic performance, maximal strength, and high-intensity power and peak stroke in elite male rowers compared to a placebo and to a BR supplementation.